P531 SARS-CoV-2 infection in Elderly patients with Inflammatory Bowel Disease with or without immunosuppressants during the first year of the pandemic. An observational, descriptive, cohort study. (27th May 2021) - Calafat Sard, M; González-Muñoza, C; Fortuny, M; Roig, C; Calm, A; Mombiela, A; Teller-Martin, M; Cañete, F; Bertoletti, F; González-González, L; Gordillo, J; Mañosa, M; et al.
Abstract: Background: Older age has been confirmed as a risk factor for severe clinical presentation of SARS-CoV-2 disease (COVID-19). The prevalence of confirmed SARS-CoV-2 infection in Catalonia among people over 60 years is 6.6%. Biological agents have not been associated with a higher incidence nor a worse prognosis of COVID-19. However, the role of immunosuppressants (IMS) on this issue is still to be elucidated. Moreover, there are scarce data related about COVID-19 in inflammatory bowel disease (IBD) patients under IMS, and none focusing in elderly IBD. Our ai m was to describe and to compare the incidence and severity of COVID-19 in patients over 65 years of age with IBD, particularly in relation to the use of IMS. Methods: We performed a retrospective cohort study including IBD patients over 65 years since January 2020, from two referral centres in the Barcelona metropolitan area (Catalonia, Spain). Patients were grouped in two cohorts regarding the use or not of IMS (thiopurines or methotrexate). Patients on biological treatment were excluded. We identified those cases with confirmed infection with SARS-CoV-2 (positive PCR) during the period from 1 st of March 2020 (the beginning of the pandemic in Catalonia) to 1 st March 2021 (the beginning of vaccination in the elderly). Demographic data, IBD comorbidities, concomitant non-IBD related treatments, and SARS-CoV-2 infection outcomes were recorded. Results: Four-hundred and eighteen elderly IBD patients were included. The median age was 74 years (IQR 69–78), 52% were male; 70% had ulcerative colitis, 28% Crohn's disease and 2% IBD unclassified, 62% had arterial hypertension, 22% diabetes mellitus, 22% cardiovascular disease, 15% chronic obstructive pulmonary disease, 10% chronic renal disease, 5% were active smokers. There were no differences regarding comorbidities and non-IBD treatments between the two study groups. From the whole cohort, 89 (21.3%) patients were on IMS (86 with thiopurines, 3 with methotrexate). The median time on IMS was 121 months (IQR 60–162). During the study period, 32 patients (7.7%) had confirmed SARS-CoV-2 infection (7 of whom were on IST; 7.6% not on IMS vs. 7.9% on IMS, P=0.933). Seventeen (53%) patients required hospital admittance (4% not IMS vs. 4.5% on IMS; P=0.818); 4 of them developed COVID-19 related complications (3 patients not on IMS vs. 1 on IMS), and 7 (22%) patients died (6 not on IMS vs . 1 patient on IMS). Conclusion: The rate of SARS-CoV-2 infection among elderly IBD patients is quite similar to that reported in the elderly background population. In elderly IBD patients, SARS-CoV-2 infection was associated with a high admission rate and mortality, regardless of the use of IMS.